Frequency of Risk Factors of Coronary Heart Diseases in Patients with Acute Coronary Syndrome and its Comparison in Male and Female - Mazhar, Naqash; Khan, Usman Hassan; Mand, Bakhat; Rehman, Abdur; Mubeen, Maryam; Malik, Mohammad Hamza Bin Abdul; Hussain, Syed Anas (Archives of Clinical and Biomedical Research, 2023)
Introduction: Cardiovascular disease (CVD) is a group of diseases that include both the heart and blood vessels, thereby including coronary heart disease (CHD) and coronary artery disease (CAD), and acute coronary syndrome (ACS) among several other conditions. Objectives: The main objective of the study is to find the frequency of risk factors of coronary heart diseases in patients with acute coronary syndrome and its comparison in male and female. Material and Methods: This cross-sectional study was conducted in Services Institute of medical sciences during June 2021 to June 2022. The data was collected with the permission of ethical committee of hospital. Results: The data was collected from 100 male and female patients. The mean age was 45.67±2.89 years for males and 49.89±5.67 years for females. The major risk factors for diseases is hypertension, hyperlipidemia, smoking and diabetes. According to data all the patients must contain one of these major risk factors and many of the patients had more than one risk factors. Conclusion: It is concluded that all the patients must have one of the major risk factors as a cause of diseases. Women with acute coronary syndrome, as compared to men, have more prevalence of diabetes and hypertension, and less prevalence of smoking.